Correlation of The Application of Teaching At The Right Level (Tarl) With Students' Basic Literacy Outcomes - Noviandi Saputra; Aswasulasikin, Aswasulasikin; Aziz, Abdul; Lestarini, Yuniar (IJE : Interdisciplinary Journal of Education, 2024)
This study aims to identify the correlation between the implementation of the TaRL (Teaching at the Right Level) approach and the improvement of grade I students' basic literacy learning outcomes. Using a quantitative correlational method, the study involved 25 students grouped into four ability levels: Special Intervention, Basic, Proficient and Advanced. The test results showed that 17 students were at the Special Intervention level, 1 student at the Basic level, 7 students at the Advanced level and none at the Proficient level. Meanwhile, to get data on learning outcomes, students were given multiple choice questions to measure their abilities. Data analysis using the Pearson Product Moment test showed a correlation value of 0.812, which is higher than the critical value of 0.396 at the 5% significance level. This indicates a very strong correlation between the application of TaRL and the improvement of basic literacy learning outcomes based on correlation interpretation. Thus, the null hypothesis (H0: no correlation) is rejected, and the alternative hypothesis (H1 : correlation) is accepted. In conclusion, the application of the TaRL approach is positively related to the improvement of students' basic literacy learning outcomes, demonstrating the effectiveness of this approach in literacy learning.